Truth worth dying for: parrhesia in Lauren Oliver's novel “Before I Fall” - Федосова, Марія Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The post-truth ideology seems to question the possibility of credibility in present-day society; however, the very idea of truth remains potent. In this paper, we adopt the notion of parrhesia, or the mode of telling the uncomfortable truth without deceit and concealment, to analyze how the discourse of truth is presented in contemporary fiction. Avoiding its political aspects, we limit our study to the interpersonal level of parrhesia that shapes individuals as moral subjects and belongs to the domain of ethos. We select Lauren Oliver's novel “Before I Fall” for analysis because it resembles a confession that involves the characters and readers in the practice of truth-telling. Drawing from Foucauldian theory, we examine how the protagonist participates in the parrhesiastic game and how the truth transforms her after she completes the stages of search for the truth, test of the character, and care for oneself and others. We argue that in the novel truth-telling is related to the problems of school bullying, social separateness, and suicide. Through the rhetorical approach to narrative we show how narration reflects psychological and moral changes of the protagonist and examine how narrative judgments reveal the ethical values of the author and the readers. We analyse how the novel describes the problem of violence demonstrating that its source lies within the family and school where abusive adolescent conduct is caused by the inability of adults to create a healthy climate for children. Individuals deprived of emotional support and guidance tend to direct their rage and frustration towards others to reduce inner strain. Lauren Oliver demonstrates the effectiveness of the parrhesiastic practice in renewing social bonds between interlocutors and reducing violent behavior. We conclude that the novel establishes truth as the highest ethical value that includes developing a true self, leading a true life according to the principles and having courage to oppose false opinions of others.